Discourse an interactive museum for media, information, and communication through an embodied approach - Real, Justine T. (College of Architecture, University of the Philippines Diliman, 2025)
This CDP addresses one of the most pressing problems globally and the most divisive in our country -- information disorder, a collective term used for disinformation, misinformation and malinformation. The development in media and information technology has and continuously shapes the media landscape in the Philippines particularly with how information is produced, distributed, and consumed. Despite these developments and wealth of local media content and information, there are no memory institutions in the country that specifically highlights Philippine mass media, its histories and narratives which makes Filipinos more susceptible to 'fake news'.